Interbellum literature : writing in a season of nihilism - Hermans, Cornelis Andreas Marie (Literary modernism (Leiden), 2017)
In Interbellum Literature historian Cor Hermans presents a panorama of modernist writing in the ominous period 1918-1940. The book offers, in full scope, an engaging synthesis of the most stimulating ideas and tendencies in the novels and plays of a wide circle of writers from France (Proust, Gide, Camus, Céline, Tzara, Aragon, Simone Weil), England and Ireland (Virginia Woolf, Orwell, Joyce, Beckett), the USA (Scott Fitzgerald, Arthur Miller, O'Neill, Hemingway), Austria-Hungary (Musil, Broch, Kafka, Zweig, Roth), and Germany (Hesse, Jünger, Böll, Thomas Mann). Caught between world wars, they nevertheless succeeded in creating some of the best literature ever. They created a philosophy as well, rejecting bourgeois 'mechanical' society, designing escape routes from the nihilism of the times.